1998
DOI: 10.1101/gad.12.12.1917
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPβ, but not C/EBPα, is essential for ductal morphogenesis, lobuloalveolar proliferation, and functional differentiation in the mouse mammary gland

Abstract: The CCAAT/enhancer binding proteins (C/EBPs) are differentially expressed throughout mammary gland development and interact with binding sites within the promoter of a milk protein gene, ␤-casein. The specific roles of C/EBP␤ and C/EBP␣ in mouse mammary gland development and differentiation have been investigated in mice that carry targeted deletions of these genes. C/EBP␤ −/− virgin mice exhibited cystic, enlarged mammary ducts with decreased secondary branching. Transplantation of C/EBP␤ −/− mammary epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
208
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(217 citation statements)
references
References 54 publications
9
208
0
Order By: Relevance
“…Moreover, these transcription factors have been shown to act cooperatively on other promoters such as that of CDllc in myeloid cells (Lopez-Rodriguez et al, 1997) and the placenta-specific trophoblast gene PLAC-1 (Koslowski et al, 2009). C/EBPβ is essential to mouse mammary gland development (Seagroves et al, 1998;Seagroves et al, 2000) as well as other processes such as mouse adipocyte differentiation (Tang and Lane, 1999). C/EBPβ −/− mice display overexpression and disruption of cellular PR expression that coincides with a 10-fold decrease in mammary cell proliferation following steroid stimulation (Seagroves et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these transcription factors have been shown to act cooperatively on other promoters such as that of CDllc in myeloid cells (Lopez-Rodriguez et al, 1997) and the placenta-specific trophoblast gene PLAC-1 (Koslowski et al, 2009). C/EBPβ is essential to mouse mammary gland development (Seagroves et al, 1998;Seagroves et al, 2000) as well as other processes such as mouse adipocyte differentiation (Tang and Lane, 1999). C/EBPβ −/− mice display overexpression and disruption of cellular PR expression that coincides with a 10-fold decrease in mammary cell proliferation following steroid stimulation (Seagroves et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A data base search to identify candidate transcription factors that may bind the p53 promoter within the Ϫ972/Ϫ953 region as well as some preliminary DNA-binding assays revealed one factor (C/EBP␤) as a likely candidate. C/EBP␤ is a CCAAT enhancer-binding protein and is critical for normal proliferation and differentiation of mammary epithelial cells (29,30,34,38) as well as numerous other cell types (27,28). It has also been shown to transactivate the c-fos serum response element upon activation of the Ras-dependent signaling pathway in response to mitogenic stimulation (31).…”
Section: Discussionmentioning
confidence: 99%
“…Here we have demonstrated that the transcription factor C/EBP␤ (CAAT/enhancer-binding protein-␤) binds to this regulatory site on the p53 promoter in response to mitogen stimulation and serves to increase p53 promoter expression as cells enter S phase. Because C/EBP␤ is a transcription factor that is critical for normal proliferation and differentiation of a number of cell types (27)(28)(29)(30) and has also been demonstrated to play a role in mitogen-stimulated induction of cell division (31), we have carried out a experiments to establish whether it also has a role in regulating p53.…”
mentioning
confidence: 99%
“…Expression of the transgene was assessed by Northern analysis of RNA extracted from adult tissues. Whole-mount analysis of mammary glands taken from virgin mice at various phases of the reproductive cycle was performed as described (Seagroves et al 1998). …”
Section: Generation and Analysis Of Transgenic Animalsmentioning
confidence: 99%